Catalytic Transformation of Cellulose and Its Derivatives into Functionalized Organic Acids. Issue 13 (15th June 2018) - Li, Shi; Deng, Weiping; Wang, Shanshan; Wang, Pan; An, Dongli; Li, Yanyun; Zhang, Qinghong; Wang, Ye
Abstract: Cellulose is a promising renewable and abundant resource for the production of high‐value chemicals, in particular, organic oxygenates, because of its high oxygen/carbon ratio. The sustainable production of hydroxycarboxylic acids and dicarboxylic acids, such as gluconic/glucaric acid, lactic acid, 2, 5‐furandicarboxylic acid, adipic acid, and terephthalic acid, most of which are monomers of key polymers, have attracted much attention in recent years. The synthesis of these organic acids from cellulose generally involves several tandem reaction steps, and thus, multifunctional catalysts that can catalyze the selective activation of specific C−O or C−C bonds hold the key. This review highlights recent advances in the development of efficient catalytic systems and new strategies for the selective conversion of cellulose or its derived carbohydrates into functionalized organic acids. The reaction mechanism is discussed to offer deep insights into the regioselective cleavage of C−O or C−C bonds. Abstract : Going green : Hydroxycarboxylic acids and dicarboxylic acids are important monomers for key polymers. The sustainable synthesis of these functionalized organic acids has attracted much research attention. Recent advances in the catalytic transformations of cellulose and its derivatives into various hydroxy‐ and dicarboxylic acids are highlighted.